The efficacy and safety of Chinese herbal medicine as an add-on therapy for amyotrophic lateral sclerosis: An updated systematic review and meta-analysis of randomized controlled trials - Liao, Yingdi; He, Sijin; Liu, Duo; Gu, Lihua; Chen, Qigang; Yang, Shuang; Li, Daiying (Frontiers in Neurology, 2022)
Background Amyotrophic lateral sclerosis (ALS) has attracted widespread attention because of its unknown pathogenesis, rapid progression, and life-threatening and incurable characteristics. A series of complementary therapies, including Chinese herbal medicine (CHM), is available for use in the clinic and has been the focus of much research. However, it is unclear as to whether supplementary CHM relieves disease symptoms or extends life span; thus, we conducted this updated meta-analysis to validate the efficacy and safety of this practice. Methods We searched six electronic databases for randomized controlled trials involving CHM and patients with ALS that were published up to April 2022. Two researchers independently screened the literature, assessed the risk of bias for each trial, and then extracted data. The methodological quality of the included trials was assessed using the Cochrane risk of bias tool, and a pooled data analysis was performed using RevMan 5.3. Results A total of 14 trials led to the publication of 15 articles featuring 1,141 participants during the study period; the articles were included in the systematic review. In terms of increasing ALS functional rating scale (ALSFRS) scores, CHM was superior to the placebo after 3 months of treatment [mean difference (MD):0.7; 95% CI:0.43 to 0.98; P < 0.01] and to riluzole after 4 weeks of treatment (MD: 2.87; 95% CI: 0.81 to 4.93; P < 0.05), and it was superior to conventional medicine (CM) alone when used as an add-on therapy after 8 weeks of treatment (MD: 3.5; 95% CI: 0.51 to 6.49; P < 0.05). The change in the modified Norris score (m-Norris) from baseline to the end of more than 3 months of treatment was significantly different when compared between the CHM plus CM group and the CM alone group (MD: 2.09; 95% CI: 0.62 to 3.55; P < 0.01). In addition, CHM had a significantly better effect on increase in clinical effective rate (RR: 1.54; 95% CI: 1.23 to 1.92; P < 0.01) and improvement in forced vital capacity (MD: 7.26; 95% CI: 2.92 to 11.6; P < 0.01). However, there was no significant difference between the CHM therapy and CM in terms of improving life quality (MD: 5.13; 95% CI: −7.04 to 17.31; P = 0.41) and decreasing mortality (RR: 0.41; 95% CI: 0.04 to 4.21; P = 0.46). Conclusion The analysis suggested that the short-term adjunct use of CHM could improve the ALSFRS score and clinical effect with a good safety profile when compared with the placebo or riluzole alone. However, future research should be centered on the long-term efficacy of patient-oriented outcomes. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=323047, identifier: CRD42022323047.